Peran Sukuk Negara di dalam Bidang Pendidikan - Taqwim Alfariz, Ahmad; Dipa Perkasa, Dokki; Azhari Hasibuan, Ishaq (Journal of Comprehensive Science, 2025)
Education has an important role in the progress of a nation, and to achieve this, the Government of Indonesia allocates education funds through various financing instruments, one of which is State Sharia Securities (SBSN). This study aims to analyze SBSN's contribution in funding the education sector, especially in increasing capacity and participation at the primary, secondary, and higher education levels. The research method used is qualitative descriptive with a secondary data analysis approach taken from correspondence with the Ministry of Education and the Ministry of Religion, as well as data related to trends in the number of students, students, and educational capacity from 2020 to 2022. The results show that SBSN has made a significant contribution to the development of educational infrastructure, including an increase in the number of students and capacity, although there are still major challenges in repairing damaged educational facilities. In conclusion, although SBSN has played an important role in the education sector, there is still more room to maximize the use of SBSN funds to support the improvement of quality and access to education, in line with the SDGs targets in the education sector.